SOSIALISASI KESEHATAN MENTAL PADA REMAJA DI BKKBN SUMSEL - Hidayat, Rahmat (CV. Alina, 2023)
In the adolescent development period, adolescents are often faced with psychological changes experienced by adolescents and mental health problems and involve many things, including psychology, emotions, anxiety. Mental health and health in general are the right of every human being. to get correct and complete knowledge about mental health is very important to achieve optimal mental health and this also applies to aspects of mental health in adolescents. The method used, especially the socialization method, is to disseminate information about mental health, mental health socialization activities for adolescents to improve the quality of life and quality of mental health in adolescents, especially around psychology, is a way to provide insight and information about healthy living behavior to PIK-R adolescents.